Beyond the notion of security community: What role for the African regional organizations in peace and security? - Liisa Laakso (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
African regional organizations' increasing activity in security policy is usually approached through the concept of a `security community', which can only partially clarify their difficult situation. A multilevel governance model is suggested as a more useful approach in a situation where economic cooperation is weak, member states' principles of governance diverge, and they themselves might be part of security problems. Security community is not a necessary condition for a regional organization to play a role in the field of security. By new intra-regional and cross-level relationships with the international community and civil society, regional organizations can become important security actors in Africa.
Keywords: F02; O19; R11; 330; African Union; regional economic communities; integration; multilevel governance; security community